POTENTIAL OF LOCAL ORIGINAL INCOME IN THE CONTEXT IMPLEMENTING REGIONAL AUTONOMY IN SERANG CITY - Lia Riesta Dewi; Azmi Polem; Eki Furqon (Universitas Serang Raya, 2024)
Serang City has the authority to explore its revenue potential in various sectors to increase the Regional Original Income (PAD) in Serang City. PAD is a revenue receipt that exists in each region and is taken based on the statutory policies that have been set by the regional government, especially on regional taxes and regional levies. The fundamental change regarding sports venue levies between Law Number 1 of 2022 and Law Number 28 of 2009 lies in the scope of sports venues that can be subject to levies. Article 136 of Law Number 28 of 2009 states that only sports venues provided, owned, and/or managed by the regional government can be subject to levies. Article 88 of Law Number 1 of 2022 does not offer such limitations. This article aims to find out what the potential regional income is from the sports sector, especially in Serang City and what are the obstacles and barriers for the Serang City regional apparatus to obtain regional original income in the sports sector, using empirical legal research methods. The potential for local revenue owned by Serang City is one of them in the sports sector, in which the Serang City government has not been able to receive PAD. The obstacle that is of concern is the lack of entry of the new legal basis that is currently ratified by the central government regarding Sports as stated in Law Number 1 of 2022 concerning Financial Relations between the Central Government and Regional Governments, and Law Number 11 of 2022 concerning Sports into regional regulations, especially legal products belonging to the Serang City Regional Government